Low-acuity presentations to the emergency department in Canada: exploring the alternative attempts to avoid presentation. Issue 4 (24th November 2016) - Krebs, Lynette D; Kirkland, Scott W; Chetram, Rajiv; Nikel, Taylor; Voaklander, Britt; Davidson, Alan; Holroyd, Bryn; Villa-Roel, Cristina; Crick, Katelynn; Couperthwaite, Stephanie; Alexiu, Chris; Cummings, Garnet; et al.
Abstract : Objective: ED visits have been rising year on year worldwide. It has been suggested that some of these visits could be avoided if low-acuity patients had better primary care access. This study explored patients' efforts to avoid ED presentation and alternative care sought prior to presentation. Methods: Consecutive adult patients presenting to three urban EDs in Edmonton, Canada, completed a questionnaire collecting demographics, actions attempted to avoid presentation and reasons for presentation. Survey data were cross-referenced to a minimal patient dataset containing ED and demographic information. Results: A total of 1402 patients (66.5%) completed the survey. Although 89.3% of the patients felt that the ED was their best care option, the majority of patients (60.1%) sought alternative care or advice prior to presentation. Men, individuals who presented with injury only, and individuals with less than a high school education were all less likely to seek alternative care. Alternative care actions included visiting a physician (54.1%) or an alternative healthcare professional (eg, chiropractor, physiotherapist, etc; 21.2%), calling physician offices (47%) or the regional health information line (13%). Of those who called their physicians, the majority received advice to present to the ED (67.5%). Conclusions: Most low-acuity patients attempt to avoid ED presentation by seeking alternative care. This analysis identifies groups of individuals in the study region who are less likely to seek alternative care first and may benefit from targeted interventions/education. Other regions may wish to complete a similar profile to determine which patients are less likely to seek alternative care first.